An analysis of female students’ verbal accounts concerning situations of sexual harassment in the university context - Linhares, Yana; Laurenti, Carolina (Perspectivas em Análise do Comportamento, 2019)
Masculine domination is a cultural practice identified in various contexts, including the academic one, as illustrated by the cases of sexual harassment by male professors towards female students. This research aimed to scrutinize masculine domination practices in the academic environment by analyzing verbal accounts students posted on a Facebook page entitled “My abuser professor”, employed to specify abusive behaviors by male professors in the formal education. We conducted functional analysis from 93 accounts, which described situations of harassment in the academic scenario, out of such we identified: abusive behaviors disguised as jokes; stereotype of abusive professors; the gradual nature of the harassment; the offer of sex in exchange for grades evincing the use of contingencies of reinforcement and punishment known to the academic world. We described the effects that such abuses had for the students’ academic course, making them abandon subjects, research projects and even academic life itself; as well as the students’ behavior towards the abuser, distinctively the behavior of acquiescence, which may end up reinforcing the professor’s abusive behavior. We emphasize the importance of reporting said behaviors, as well as fostering administrative bodies in the University able to embrace, advance and discuss cases of sexual harassment.